IONOSPHERIC ELECTRIC CURRENT-SYSTEMS DERIVED USING INTERNATIONAL POLAR YEAR DATA - Vestine,E. H.; Nagata,T. (1957)
This paper summarizes something of the present state of knowledge of the electric current-systems flowing within the upper atmosphere. It is intended to supplement the accounts on the general subject of geomagnetic observations made during the Second International Polar Year, 1932-1933. Legibility of this document is in part unsatisfactory. Reproduction has been made from best available copy.